Strategy Maps as a Tool for Business-IT Strategic Alignment - Jelonek, Dorota (Mapy strategiczne jako narzędzie w dopasowaniu strategii biznesowej i strategii IT, 2010)
The aim of the paper is the presentation of strategy maps as a tool which can be used in the alignment of business strategy and the IT strategy in the enterprise. The effect of the literature studies is the presentation of the classical BSC card elaborated by Kaplan and Norton and its several modifications taking into account additional perspectives which are worth consideration in the creation of maps of strategy depending on the specificity of the enterprise. Presented examples of maps of business strategy and IT strategy can be an inspiration for particular acts of the alignment of business and IT strategy undertaken by enterprises.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2010; Nr 147, s. 160-172
Keywords: business strategy; IT strategy; strategic alignment; strategy maps